Factors Influencing Drug Shortages and Their Resolution in South Korean Community Pharmacies - Lee YH; An D; Baek Y; Yoo K; Hyun S; Park SK; Lee EK (Dove Medical Press, 2024)
Yong Hwa Lee,1,* Dasom An,1,* Youngsuk Baek,1 Kyungsook Yoo,2 Sumi Hyun,1 Sun-Kyeong Park,3 Eui-Kyung Lee1 1School of Pharmacy, Sungkyunkwan University, Suwon, Gyeonggi-do, South Korea; 2School of Pharmacy, Kangwon National University, Chuncheon, Gangwon-do, South Korea; 3College of Pharmacy, The Catholic University of Korea, Bucheon, Gyeonggi-do, South Korea*These authors contributed equally to this workCorrespondence: Sun-Kyeong Park, College of Pharmacy, The Catholic University of Korea, 43 Jibong-ro, Bucheon-si, Gyeonggi-do, 14662, South Korea, Tel +82221644094, Email sk.park@catholic.ac.kr Eui-Kyung Lee, School of Pharmacy, Sungkyunkwan University, 2066, Seobu-ro, Jangan-gu, Suwon-si, Gyeonggi-do, 16419, South Korea, Tel +82312907786, Email ekyung@skku.eduPurpose: Drug shortages directly affect the final stage in the pharmaceutical supply chain, prescription fulfillment in community pharmacies (CPs). This study investigated the current state of drug shortages, their resolution, and influencing factors within CPs.Methods: A cross-sectional online survey was conducted among pharmacists working at pharmacies in Seoul between 7 and 31 October 2022. The survey gathered data on pharmacies and pharmacists' characteristics, drug distribution, information, communication, and administrative practices. Logistic regression was used to identify the factors influencing these rates. Regression results are presented as odds ratios (OR) and 95% confidence intervals (CIs).Results: Of the 1200 pharmacists approached, 713 participated, yielding a response rate of 59.4%. After excluding incomplete responses, data from 671 respondents were analyzed. Pharmacies with higher prescription drug sales demonstrated a lower OR for drug shortages (OR=0.66, 95% CI=0.60- 0.72) compared to those with lower sales volumes. Resolution rates were significantly higher when pharmacies were located near clinics (OR=3.30, 95% CI=2.3- 4.74) and general hospitals (OR=3.45, 95% CI=2.35- 5.07) compared to those without nearby medical facilities. Additionally, good communication with prescribers increased the resolution rates (OR=1.46, 95% CI=1.26- 1.69).Conclusion: This study examines the influence of pharmacy purchasing power on drug shortages, identifying proximity to healthcare facilities and communication with prescribers as factors affecting the resolution rates. These findings provide valuable insights for pharmacists, policymakers, and future researchers to optimize drug supply chain management and mitigate shortages in community settings.Keywords: drug shortage, drug shortage resolution, community pharmacy, pharmaceutical supply chain